Permanent Genetic Resources added to Molecular Ecology Resources Database 1 August 2012 – 30 September 2012. (26th November 2012) - ,; Ahanchédé, Adam; Alfaya, José E. F.; Andersen, L. W.; Azam, Didier; Bautista, Ma. Anita M.; Besnard, Anne‐Laure; Bigatti, Gregorio; Bouétard, Anthony; Coutellec, Marie‐Agnès; Ewédjè, Eben‐Ezer B. K.; Fuseya, Reiko; et al.
Abstract: This article documents the addition of 83 microsatellite marker loci and 96 pairs of single‐nucleotide polymorphism (SNP) sequencing primers to the Molecular Ecology Resources Database. Loci were developed for the following species: Bembidion lampros, Inimicus japonicus, Lymnaea stagnalis, Panopea abbreviata, Pentadesma butyracea, Sycoscapter hirticola and Thanatephorus cucumeris ( anamorph : Rhizoctonia solani) . These loci were cross‐tested on the following species: Pentadesma grandifolia and Pentadesma reyndersii . This article also documents the addition of 96 sequencing primer pairs and 88 allele‐specific primers or probes for Plutella xylostella .